Natural and Experimental Coccidial Infection in the Malayan Red Jungle Fowl (Gallus Gallus Spadiceus) - Lee , Chu Chong (1998)

(untitled)
Wild Malayan red jungle fowl faecal samples were examined to determine the prevalence and species of Eimeria from their natural habitat. The birds possessed at least five coccidial species, namely Eimeria mitis, E. acervulina var. diminuta, E. praecox var. ceylonensis, E. maxima var. indentata and an unidentified Eimeria species. No attempt was made to name this unidentified species as information on other stages was lacking. Intensively reared Malayan red jungle fowl chicks were used to study the pattern of coccidial infections. The chicks suffered from coccidiosis caused by E. tenella, E. necatrix and E. maxima. The mean prepatency period in these chicks was 9 days; their peak oocyst counts ranged from 136, 364 to 591, 200 oocysts per gram of faeces. Eimeria tenella was the most prominent pathogenic species encountered. Kamovsky's fixative and McNamara's Giemsa stain were used for the first time for processing mucosal tissue samples for the study of cellular response to E. tenella. Two groups of laboratory hatched chicks were each infected orally with E. tenella (NIAH, Japan strain) with either 15,000 or 30,000 oocysts whilst the third group remained as controls. Eosinophils increased significantly (P<0·05) while mast cells declined significantly (P<0·05) from day-5 to day-7 post infection. The cell types recognised in the caecal mucosae were ultrastructurally quite similar to those reported from the domestic chicken. Most mast cell granules were surrounded by halos in various degranulating stages. The eosinophils had regular membrane bound dense granules. The heterophils possessed large, oval to spindle dense granules, small round to oval dense granules and small light, round to spindle granules. Mononuclear cells had proportionally large distinct double wall nuclei. The cytoplasm of lymphocyte contained prominent round mitochondriae whilst that of the plasma cell was packed with several strands of endoplasmic reticulum. This study showed that jungle fowls could suffer from coccidiosis when domesticated. However, proper management together with the necessary supportive treatment with drugs could be effective against such infections.